2013
DOI: 10.1093/ajh/hpt152
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Overweight Associated With Increased Carotid Diameter and Decreased Arterial Function in Young Otherwise Healthy Men

Abstract: Obesity is associated with a much worse arterial profile, as an increased carotid lumen size was accompanied by higher blood pressure, greater arterial stiffness, and greater carotid intima media thickness in obese compared with overweight or normal-weight individuals. These data suggest that although obesity may be a factor in arterial remodeling, such remodeling is also accompanied by other hemodynamic and arterial changes consistent with reduced arterial function and increased cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 43 publications
5
34
1
2
Order By: Relevance
“…; Kappus et al. ). We also observed higher resting brachial (DBP and MAP) and central BP (SBP, DBP, and MAP) and cPWV in obese individuals compared with normal‐weight individuals.…”
Section: Discussionmentioning
confidence: 98%
“…; Kappus et al. ). We also observed higher resting brachial (DBP and MAP) and central BP (SBP, DBP, and MAP) and cPWV in obese individuals compared with normal‐weight individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Esse último grupo (C/ ag) demonstrou menor espessura do vaso quando comparado aos animais obesos (O/ag e O/co), porém estes valores não são estatisticamente relevantes. Outros estudos demonstram que a obesidade está associada com aumento da espessura da túnica média (KAPPUS et al, 2014;VAN DRONGELEN et al, 2012), podendo não ter sido demonstrado de maneira estatisticamente significativa em nosso estudo devido ao reduzido tamanho dos grupos. A administração de óleo de coco levou a um pequeno aumento da espessura do vaso tanto nos animais controles como nos obesos, sendo o aumento mais pronunciado entre os animais controles, porém esse aumento não foi estatisticamente significativo.…”
Section: Resultsunclassified
“…Intuitively one would think that obesity, being related to higher cardiovascular risk would be positively related to elevated arterial stiffness. However the literature shows conflicting data [28][29][30][31][32]. In their review about risk factors associated with PWV, Cecelja et al found that only 13% of the relevant publications reported a positive association between BMI and PWV [4].…”
Section: Discussionmentioning
confidence: 99%
“…In their review about risk factors associated with PWV, Cecelja et al found that only 13% of the relevant publications reported a positive association between BMI and PWV [4]. Several authors reported a negative association [33,34] or no association [30][31][32]. Indeed overestimation of the arterial path length or clinical confounders of obesity could skew results.…”
Section: Discussionmentioning
confidence: 99%